Analysis of Academic Burnout and Its Impact on Students’ Mental Health - Hainrich, Hainrich; Raclaw, Mateusz (Acta Psychologia, 2026)
Analysis of Academic Burnout and Its Impact on Students’ Mental Health This study examines academic burnout and its impact on students’ mental health, with a focus on identifying its prevalence, contributing factors, and psychological consequences. Academic burnout is conceptualized as a multidimensional condition characterized by emotional exhaustion, cynicism toward academic activities, and reduced academic efficacy. Using a quantitative research design, data were collected from students through standardized questionnaires measuring burnout and mental health indicators. Statistical analyses, including correlation and regression, were employed to examine the relationship between variables. The findings reveal that a significant proportion of students experience moderate to high levels of academic burnout. The results further indicate a strong and significant relationship between academic burnout and mental health outcomes, showing that higher levels of burnout are associated with increased psychological distress. In particular, burnout is found to significantly predict symptoms of Stress, Anxiety Disorder, and Depression. Additionally, key contributing factors identified in this study include academic overload, lack of social support, and poor time management, which interact through a psychological mechanism where prolonged stress leads to emotional exhaustion and subsequent mental health problems. The study contributes to the theoretical development of academic burnout by integrating internal and external influencing factors into a comprehensive framework. Practically, the findings provide important implications for educational institutions to design interventions aimed at reducing burnout and promoting student well-being. These include improving workload management, enhancing social support systems, and implementing mental health awareness programs. Overall, this research highlights the urgent need to address academic burnout as a critical issue affecting both academic performance and students’ psychological health.